2018
DOI: 10.1097/icl.0000000000000386
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Impacts of Orthokeratology Treatment on Sub-Basal Nerve Plexus and Corneal Sensitivity Responses and Their Reversibility

Abstract: Abstract:PURPOSE: To examine the effects of 1 year of overnight orthokeratology (OK) treatment on the sub-basal nerve plexus (SBNP) and corneal sensitivity and to assess the reversibility of these effects 1 month after treatment interruption.METHODS: 32 subjects with low-moderate myopia underwent OK treatment for one year. 15 non-contact lens wearers served as controls. At the time points baseline, 1 year of treatment, and 1 month after removing the OK lenses, two tests were conducted: corneal sensitivity (Coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
(49 reference statements)
1
7
0
Order By: Relevance
“…In a continuation of this study, she discovered an unexpected consistency in central corneal sensitivity after one year of orthokeratology relative to that before treatment and attributed it to an undefined neuronal adaptation. Her studies showed this recovery occurred between one month and one year but she combined her data with Lum's data and concluded that the recovery occurred between three months and one year [25]. The changes in central corneal sensitivity during the first month in our study are basically the same as those in previous studies, and neuronal adaptation was thought to be the main contributor to this change [24, 26].…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…In a continuation of this study, she discovered an unexpected consistency in central corneal sensitivity after one year of orthokeratology relative to that before treatment and attributed it to an undefined neuronal adaptation. Her studies showed this recovery occurred between one month and one year but she combined her data with Lum's data and concluded that the recovery occurred between three months and one year [25]. The changes in central corneal sensitivity during the first month in our study are basically the same as those in previous studies, and neuronal adaptation was thought to be the main contributor to this change [24, 26].…”
Section: Resultssupporting
confidence: 78%
“…However, our findings show that the recovery of corneal sensitivity occurred within 3 months of OK treatment. This is not consistent with Nombela-Palomo's conclusion [25]. Neuronal adaptation is the time-dependent modulation of sensory responses following sequential stimuli and thought to be a consequence of synaptic plasticity [28].…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Central sensitivity is reduced by approximately 50 % and recovers to pre-lens wear levels after cessation of lens wear [367][368][369]. Corneal nerve morphology is affected by ortho-k, with a reduction in nerve fibre density and re-organisation of the nerve fibre orientation [368][369][370][371][372]. The nerve fibre changes also resolve with cessation of ortho-k lens wear, in sync with the recovery in sensitivity [369,372].…”
Section: Sensitivity and Nerve Changesmentioning
confidence: 96%